Pandangan Islam Terhadap Pasal Penistaan Agama - Abdul Aziz (Program Pascasarjana Universitas Ibrahimy, 2018)
Freedom in certain religions has been guaranteed by law. This freedom should not interfere another people's freedom. To realize this kind of freedom then the law appears to regulate the prohibition of insulting or defamating a particular religion. When the state has provided a provision in the matter of blasphemy, what is about Islam? To find the answer of this question, ought to look at the Qur’an, the Hadith and the opinions of Fuqaha. The conclusion obtained that the article contained in the Criminal Code is in accordance with the doctrine of Islam. Islam always teach moslems to appreciate what other people trust meanwhile when there are people who insult at Islam, such as insulting Allah and Prophet, so must be consequent as murtad and be killed.